Rates of Change to a Positive Result in Subsequent Screening Mammography in Korean Women: A Retrospective Observational Study - Jong-Myon Bae; Sang Yop Shin; Eun Hee Kim; Yoon-Nam Kim; Chung Mo Nam (Korean Society for Preventive Medicine, 2015)
Objectives: This retrospective cohort study aimed at calculating some parameters of changes in the findings of the subsequent screening mammography (SSM) in female Korean volunteers. Methods: The study included screenees aged 30 to 79 years who underwent SSM voluntarily after testing negative in the baseline screenings performed between January 2007 and December 2011. A change to a positive result was defined as category 4 or 5 by using the American College of Radiology Breast Imaging Reporting and Data System. The proportion of results that had changed to positive (CP, %) was calculated by dividing the number of cases with results that were positive in the SSM by the total number of study participants. The rate of results that had changed to positive (CR, cases per 100 000 screenee-months) was calculated by dividing the number of cases with results that were positive in the SSM by the total number of months of the follow-up period. Results: The overall CP and CR in all age groups (n=77 908) were 2.26% and 93.94 cases per 100 000 screenee-months, respectively. The median CP interval in the subjects who had positive SSM results was 30 to 36 months, while that in the age group of 30 to 39 years was shorter. Conclusions: Different screening intervals should be considered among women aged between 30 and 59 years. In addition, a strategy for a screening program should be developed for the age group of 30 to 39 years, in particular.